III-V/Si Hybrid Laser Stabilization Using Micro-Ring Feedback Control - Jin-Hyoung Lee; Daniel Y. Lee; Ivan Shubin; Jock Bovington; Stevan S. Djordjevic; Shiyun Lin; Ying Luo; Jin Yao; John E. Cunningham; Kannan Raj; Ashok V. Krishnamoorthy; Xuezhe Zheng (IEEE Photonics Journal)
We present a real-time approach for stabilizing a III-V/Si hybrid external-cavity laser implemented using microring monitoring and a feedback control loop. Laser mode stabilization over bias current and stage temperature variations are experimentally demonstrated. We achieved single-mode and mode-hop-free laser operation as the bias current was swept across 320 mA. The same feedback control also enabled wavelength-locked laser operation using an intracavity phase control. The feedback control was also applied to an integrated on-chip hybrid laser, and mode-hop-free laser operation was demonstrated over 23 °C substrate temperature variation.